Digital karyotyping - Wang, Tian-Li (National Academy of Sciences, 2002)
Alterations in the genetic content of a cell are the underlying cause of many human diseases, including cancers. We have developed a method, called digital karyotyping, that provides quantitative analysis of DNA copy number at high resolution. This approach involves the isolation and enumeration of short sequence tags from specific genomic loci. Analysis of human cancer cells by using this method identified gross chromosomal changes as well as amplifications and deletions, including regions not previously known to be altered. Foreign DNA sequences not present in the normal human genome could also be readily identified. Digital karyotyping provides a broadly applicable means for systematic detection of DNA copy number changes on a genomic scale.